2007
DOI: 10.1100/tsw.2007.206
|View full text |Cite
|
Sign up to set email alerts
|

P-Body Components, microRNA Regulation, and Synaptic Plasticity

Abstract: What is the protein apparatus required for microRNA (miRNA) function and translational repression in neurons? This article reviews our recent work on Me31B, a conserved P-body protein present on Staufen-containing neuronal and maternal ribonucleoprotein (RNP) particles, which is required for dendrite morphogenesis and miRNA function in vivo. In addition, it provides new data to show that Me31B is present on and regulates formation of P-bodies in the Drosophila wing disc, where it has a general role in the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 84 publications
2
22
0
1
Order By: Relevance
“…* NS, nonspecific protein band. studies from several laboratories have strengthened the connection between miRNA-based regulation and PTGS in NGs (30). Here we report that Htt co-localizes with Ago2 in dendritic granules, and knockdown of Htt in dendrites results in altered Ago2 distribution.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…* NS, nonspecific protein band. studies from several laboratories have strengthened the connection between miRNA-based regulation and PTGS in NGs (30). Here we report that Htt co-localizes with Ago2 in dendritic granules, and knockdown of Htt in dendrites results in altered Ago2 distribution.…”
Section: Discussionsupporting
confidence: 56%
“…To quantitatively assess Htt co-localization with these markers we examined multiple neurons and found that Htt dendritic granules often contained DCP1 (80.6%), Staufen (57.5%), and DDX6 (52.4%) ( Table 1). NGs are generally identified by the presence of Staufen, FMRP, and DDX6 (30). We thus provide evidence that Htt is present with two of the three NG markers.…”
Section: Resultssupporting
confidence: 50%
“…dFmr1 and Atx2 orthologs in other species are present on Me31B-positive cytoplasmic mRNP aggregates related to stress granules (36,(60)(61)(62)(63). In addition, Atx2 function seems to be essential for the formation of Me31B-containing mRNP assemblies both in yeast as well as in mammalian cultured cells (39).…”
Section: Neuronal Atx2 and Dfmr1 Proteins Physically Associate And Bimentioning
confidence: 98%
“…By stage 6, the two proteins also colocalize in the oocyte cytoplasm ( Fig. 4M-P), which will eventually contain the polar granules, where Aub, dFmr1 and Vasa accumulate (Costa et al, 2005;Hillebrand et al, 2007;Thomson et al, 2008). dFmr1 does not seem to affect Aub expression, which still accumulates and localizes properly in dFmr1 ▵50 homozygous ovaries ( Fig.…”
Section: Dfmr1 and Aub Colocalize In Testis And Ovaries And Interact mentioning
confidence: 99%